ESTIMASI RELIABILITAS PENGUKURAN DALAM PENDEKATAN MODEL PERSAMAAN STRUKTURAL - Wahyu Widhiarso (Buletin Psikologi, 2009)
The utility of Structural Equation Modelling (SEM) approach into research in psychology, especially in psychometrics development have not yet been fully explored. The proportion of utilization between SEM sub models in research field (i.e. structural model and measurement model) was unbalance. Numerous researcher has used SEM only to test their structural model but avoid to use SEM to identify its measurement model. This article explain SEM function to estimate reliability of measurement. The reliability coeffcient such as composite reliability, construt reliability and maximal reliability are outlined.